Lawsonia intracellularis: Tráfego intracelular precoce e fatores de virulência. - Mirtha Elizabet Suarez Duarte (2023)
A common enteric disease known as proliferative enteropathy is caused by Lawsonia intracellularis, an obligatory intracellular bacterium. The characteristic thickening of the intestinal mucosa due to hyperplasia of intestinal epithelial cells has been reported in several animal species, however, among the most severely affected domestic species, pigs, and horses. The initial events related to the interaction between pathogen and host are not fully understood during infection by L. intracellularis, mainly the mechanism of interaction with the host cell and intracellular traffic. In this case, a new method of quantification of L. intracellularis was initially developed using optical density spectrometry. Furthermore, a study was carried out to search for orthologous genes between enteropathogenic bacteria and L. intracellularis, and the orthology of invasion and survival genes was observed due to the evasion of the lysosomal digestion system of these bacteria. An in-depth evaluation of the intracellular trafficking of L. intracellularis in immortalized intestinal epithelial cells (IEC-18) and in macrophages of primary pig origin has also been carried out, verifying co-localization of markers of early and late endosomes with L. intracellularis. Thus, the recruitment of Rab 5, Rab 7 and Cathepsin D was demonstrated in the endocytosis process of L. intracellularis in intestinal epithelial cells (IEC-18) in rats and in macrophages (swine). The results obtained in this experiment provide new data that contribute to a better understanding of the traffic and interaction between L. intracellularis and the host cell.